Extraction, Partial Purification and Utilization of Milk Coagulating Enzyme from Kiwifruit (Actinidia Deliciosa) in Fresh Cheesemaking - Maskey, Bunty; Karki, Dhan Bahadur (Himalayan Journal of Science and Technology, 2022)
The study aimed to determine the potential of kiwifruit milk clotting enzyme in cheesemaking. The kiwifruit crude enzyme, extracted with sodium phosphate buffer (pH 7.0), was partially purified by 30-80% ammonium sulfate precipitation. 50% ammonium sulfate saturation exhibited maximum milk clotting activity (MCA), along with 1.56 purification fold, and 78.84% activity recovery. From SDS-PAGE analysis, the partially purified protease showed two bands with a molecular mass of 24 kDa and 23 kDa respectively. The optimum conditions (temperature and pH of milk) for a minimum time of coagulation (TOC) and maximum MCA were determined by response surface methodology (RSM). From the numerical optimization study, the optimum conditions for cheesemaking were pH 6.5 and temperature 55oC, having 0.94 desirability. The cheese prepared by kiwifruit protease had significantly (p<0.05) higher moisture, ash, calcium content, and yield than rennet cheese, while significantly (p<0.05) lower fat content and acidity were observed in kiwifruit protease coagulated cheese. However, a non-significant (p>0.05) difference in protein content was obtained between both cheeses. This study highlighted that kiwifruit protease has the ability to be used as an efficient milk clotting enzyme in fresh cheesemaking.